Polycaprolactone/cellulose acetate loaded psidium guajava essential oil electrospun nanofibrous mat dressing for healing wounds - Nor Naimah Hussin,; Noor Suhana Adzahar,; Thong, Chuan Lee; Izan Izwan Misnon,; Jayarama Reddy Venugopal, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Natural products and essential oils of medicinal plants are extensively employed in wound healing, particularly in the pharmaceutical industry. Essential oils obtained from Psidium guajava were utilised as an antibacterial agent against Bacillus subtilis, Staphylococcus aureus, and Enterococcus faecalis, and to control drug-resistant strains. In this study, electrospinning for applications in antimicrobial activity and drug delivery systems was used to develop biocomposite nanofibers of Polycaprolactone (PCL)/Cellulose Acetate (CA) and Psidium guajava essential oil (PGEO). Images from the FESEM revealed that the mean fire diameters were 120 nm for the PCL/CA and 223 nm for PCL/CA/PGEO biocomposite nanofibers. The diameters of the nanofibers were increased following the addition of PGEO into PCL/CA nanofibers. Furthermore, FTIR studies revealed the -OH peak in pure electrospun PCL/CA and PCL/CA/PGEO, lacking pure PGEO nanofibrous mats. These findings reflect that Psidium guajava essential oil/PCL/CA electrospun nanofibers are promising candidates for presenting bioactive compounds in wound management or other approaches for wound healing and bacterial infections.